Formation of eyeball orbital stump using titanium nickelide tissue-engineered construct and autologous blood mononuclear leukocytes - E. A. Gorbunova; O. I. Krivosheina; L. R. Mustafina (Вестник трансплантологии и искусственных органов, 2020)
Objective: to study the morphological features of formation of the eyeball orbital stump using a titanium nickelide  tissue-engineered construct and a suspension of autologous blood mononuclear leukocytes in vivo. Materials  and methods. Experiments were performed on 54 sexually mature Wistar rats weighing 200–250 g. The animals   were divided into 3 groups, depending on type of surgical intervention: group 1 (n = 18) consisted of animals in  which eyeball orbital stump was formed after evisceroenucleation through implantation of a titanium nickelide  tissue-engineered construct and a suspension of autologous blood mononuclear leukocytes in the scleral sac; group  2 (n = 18) – the eyeball orbital stump was formed through implantation of titanium nickelide tissue-engineered  construct in the scleral sac; group 3 (n = 18) – orbital stump was formed using an Alloplant implant. Results.  It was established that in group 1 rats, on day 7 following surgery, the specific volume of connective tissue was  7.9 times (рU = 0.048) higher than in group 2 rats and 15.8 times (рU = 0.039) higher than in group 3 rats. On  day 14 after surgery, the volume of connective tissue in the eyeball orbital stump of group 1 rats reached the highest  value compared to that in the other groups. The numerical density of newly formed vessels in the eyeball orbital  stump of group 1 rats, starting from day 14 after surgery up to the end of experiment (day 21), was statistically  significantly higher than that in the other groups. Moreover, on day 21, this indicator was 4.0 times (рU = 0.001)  higher in group 1 rats than in group 2 rats and 9.8 times (рU = 0,0003) higher than in group 3 rats. Conclusion.  Implantation of titanium nickelide tissue-engineered construct and a suspension of autologous blood mononuclear  leukocytes into the scleral sac after evisceroenucleation in an in vivo experiment leads to accelerated maturation  of the connective tissue and intensive vascularization in the eyeball orbital stump. This ensures strong fixation of  the implant and reduces risk of rejection.